2022
DOI: 10.4102/jir.v5i1.71
|View full text |Cite
|
Sign up to set email alerts
|

Curing the pandemic of misinformation on COVID-19 mRNA vaccines through real evidence-based medicine - Part 1

Abstract: Background: In response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), several new pharmaceutical agents have been administered to billions of people worldwide, including the young and healthy at little risk from the virus. Considerable leeway has been afforded in terms of the pre-clinical and clinical testing of these agents, despite an entirely novel mechanism of action and concerning biodistribution characteristics.Aim: To gain a better understanding of the true benefits and potential harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…While the effectiveness of these vaccines against severe COVID-19 has been documented in several population studies [ 2 , 3 , 4 , 5 , 6 ], some primary studies [ 7 , 9 , 10 , 11 , 23 ] and secondary analyses of serious adverse events reported (a) in the randomized clinical trials of Pfizer and Moderna mRNA COVID-19 vaccines in adults [ 16 , 24 ], (b) in the U.S.A. Vaccine Adverse Event Reporting System (VAERS) passive surveillance data [ 25 , 26 ], and (c) in the National registries of Denmark, Finland, and Norway [ 27 ], have raised concerns about the safety or risk-benefit profile of COVID-19 vaccination, especially in population subsets with the lowest infection-fatality rate [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the effectiveness of these vaccines against severe COVID-19 has been documented in several population studies [ 2 , 3 , 4 , 5 , 6 ], some primary studies [ 7 , 9 , 10 , 11 , 23 ] and secondary analyses of serious adverse events reported (a) in the randomized clinical trials of Pfizer and Moderna mRNA COVID-19 vaccines in adults [ 16 , 24 ], (b) in the U.S.A. Vaccine Adverse Event Reporting System (VAERS) passive surveillance data [ 25 , 26 ], and (c) in the National registries of Denmark, Finland, and Norway [ 27 ], have raised concerns about the safety or risk-benefit profile of COVID-19 vaccination, especially in population subsets with the lowest infection-fatality rate [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is instructive to note that the greater the financial interests in a given field, the less likely the research findings are to be true. 14 As has been already demonstrated in Part 1 15 of this article, mandating a novel emergency use authorisation vaccine to non-vulnerable people has little to no effect on preventing infection and serious illness, therefore does not have any scientific validity, and therefore breaches the principles of informed consent. It does, however, dramatically enhance the profits of the manufacturer.…”
Section: A Pandemic Of Misinformationmentioning
confidence: 86%
“…Another driver of people's move towards distrust of science has been the experience of adverse events following administration of products known as COVID-19 vaccines. The adverse event rate is significantly higher than any previously administered vaccine, and is even much higher than the rates of vaccines previously withdrawn due to safety concerns [123]. Dangers being assuaged away by public health agency without sufficient evidentiary basis to rule out these dangers violates the bedrock bioethical principle of informed consent [124].…”
Section: Bioethical Violationsmentioning
confidence: 99%